Native and Exotic Insect Borers Are Important Crop Pests in the U.S. - Daniel L. Frank; Russell F. Mizell, III (EDIS, 2006)
ENY-730, an 8-page illustrated fact sheet by Daniel L. Frank and Russell F. Mizell, III, describes the diverse families of woodboring insects, the damage they cause, and management options. Published by the UF Department of Entomology and Nematology, April 2006.